Лісівничо-селекційна оцінка насаджень сосни звичайної аціонального природного парку«Прип’ять–Стохід» - Войтюк, Василь; Андреєва, Валентина; Кичилюк, Олександр; Гетьманчук, Анатолій; Voytyuk, Vasyl; Andreyeva, Valentyna; Kychylyuk, Oleksandr; Getmanchuk, Anatoliy (Східноєвропейський національний університет імені Лесі Українки, 2015)
Досліджено селекційну цінність деревостанів сосни звичайної на території Національного природного парку «Прип’ять–Стохід». Досліджувані деревостани ростуть в умовах свіжого бору і субору за І а –II боні-тетом, здорові, віком75–90 років при повноті0,63–0,92 мають запас деревини на1 га330–460 куб. м. Значна різноманітність показників сосни звичайної дає змогу виконувати плюсову селекцію на місцевому матеріалі. The work is devoted to the study of selection values of Scotch pine foreststands in the National Park “Pripyat–Stokhid”. Investigated forest stands are growing in fresh forest and pine forestson Ia-II bonitet, characterized by good health, aged 75–90 years in the fullness of 0,63–0,92 have stock of wood per 1 ha of 330–460 cubic meters. The selection structureof trees is showed that one planting is belonging to normal andthree – to plus. Trees are characterized by good cleaning trunk of dead twigs, good and average overgrowth cleared of dead knots places. Also trees have got well developed mainly conical crowns, mostly from the middle and thin branches. In most of the trees are no defects trunk and crown. A large variety of morphological forms and variability of forest-selection indexes of Scotch pine allows carrying out the positive selection at the local material. Researched forest stands advisable to classify as genetic reserves. We propose to use plus stands in quality testing as candidatesto natural varieties-populations of Scotch pine. Key words:Scotch pine, genetic reserve, plus tree.
Forestry selection estimation of forest planting of Scotch pine in National natural park “Pripyat–Stokhid”
Keywords: сосна звичайна; генетичний резерват; плюсове дерево; Scotch pine; genetic reserve; plus tree